2009
DOI: 10.3390/molecules14062286
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Liquids in Tribology

Abstract: Current research on room-temperature ionic liquids as lubricants is described. Ionic liquids possess excellent properties such as non-volatility, non-flammability, and thermo-oxidative stability. The potential use of ionic liquids as lubricants was first proposed in 2001 and approximately 70 articles pertaining to fundamental research on ionic liquids have been published through May 2009. A large majority of the cations examined in this area are derived from 1,3-dialkylimidazolium, with a higher alkyl group on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
540
0
6

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 620 publications
(561 citation statements)
references
References 76 publications
15
540
0
6
Order By: Relevance
“…Accordingly good antiwear properties, hydrolytic stability and hydrophobicity of the [NTf 2 ] anion reported by Minami et al [16,30]. This paper studies the effectiveness of using two ionic liquids …”
Section: *Manuscript Click Here To View Linked Referencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly good antiwear properties, hydrolytic stability and hydrophobicity of the [NTf 2 ] anion reported by Minami et al [16,30]. This paper studies the effectiveness of using two ionic liquids …”
Section: *Manuscript Click Here To View Linked Referencesmentioning
confidence: 99%
“…Different FAP-anion based ILs have been studied both as additive and as a neat lubricant for different materials pairs exhibiting excellent friction and wear reducer behaviour [20][21][22][23][24][25][26]. Some review papers [29][30][31][32] have detailed the advantages of using ILs in tribology, their thermal and oxidative stability, and their tribochemical reactions.…”
Section: *Manuscript Click Here To View Linked Referencesmentioning
confidence: 99%
“…A lot of researches have been published concerning the use of ionic liquids as lubricants since 2001 [29], proving their remarkable potential for this purpose [4,6,[30][31][32]. At the beginning, imidazolium-based ionic liquids with [PF 6 ] and [BF 4 ] anions were widely used [33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…Since then, there have been numerous reports on similar applications have been published in international tribology journals. Thus far, the relationship between the chemical structure and the tribological properties of RT-ILs has been fundamentally studied [9][10][11]; it has been observed that hydrophobic anions (e.g., TFSA) afforded better tribological properties to RT-ILs than the hydrophilic anions (e.g., BF 4 ) [12,13]. Higher alkyl groups in imidazolium cations are instrumental in improving the tribological properties of a compound.…”
Section: Introductionmentioning
confidence: 99%
“…However, in tribology, the main anions under consideration are BF 4 , PF 6 , and TFSA. Most literatures on cationic moieties deal with imidazolium derivatives [9]. From a chemical perspective, alkylimidazolium cations are versatile building blocks of cationic moieties having bulky and asymmetrical skeletons.…”
Section: Introductionmentioning
confidence: 99%